2011
DOI: 10.1590/s0102-33062011000300021
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da diversidade arbórea das ilhas do rio Paraguai na região de Cáceres, Pantanal Matogrossense, Brasil

Abstract: ABSTRACT(Assessment of tree diversity on the islands of the Paraguay River, in the Caceres region, Pantanal, Brazil). Plant diversity on islands is associated with habitat heterogeneity, the distribution of a species, the flood pulse that may be influenced by fluvial dynamics and differences in geomorphologic origin. This study assessed the diversity of trees on six islands of the Paraguay River, between Caceres and Taimã Ecological Station, in the Pantanal, Brazil. Islands created by two geomorphologic proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
1
5
0
4
Order By: Relevance
“…ATTZs composed of forested areas contained the greatest number of bird species. Islands in this region of the Paraguay River usually have high levels of tree diversity (Ikeda-Castrillon et al 2011), and become habitats and the source of essential resources for even the most demanding birds, with regard to use of different vertical strata within the wetland environment. Grasslands had lower levels of observed richness than forest areas, possibly due to the limited number of places, such as perches in trees and shrubs, that provide shelter for species throughout the forest strata (Almeida et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ATTZs composed of forested areas contained the greatest number of bird species. Islands in this region of the Paraguay River usually have high levels of tree diversity (Ikeda-Castrillon et al 2011), and become habitats and the source of essential resources for even the most demanding birds, with regard to use of different vertical strata within the wetland environment. Grasslands had lower levels of observed richness than forest areas, possibly due to the limited number of places, such as perches in trees and shrubs, that provide shelter for species throughout the forest strata (Almeida et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The responses of biological communities to the spatial and temporal variation within ATTZs are still poorly understood. Some studies have shown that terrestrial and aquatic biological communities such as vegetation (Ikeda-Castrillon et al 2011, Catian et al 2018, vertebrate animals (Figueira et al 2011, Lázari et al 2013, Valério et al 2016, Penha et al 2017 and invertebrates (Oliveira-Júnior et al 2013) can respond differently to landscape changes caused by flood and dry cycles of the Pantanal.…”
Section: Introductionmentioning
confidence: 99%
“…Jacq. ex Scop., Triplaris americana L., Sapium obovatum Klotzsch ex Mull, Spondias mombin L. and Inga vera Willd., common in the Paraguay River islands (Ikeda-Castrillon et al 2011). Another type of area on this transect is (3) floating marshes, formed by layers of floating organic matter (remnants of aquatic vegetation, roots and rhizomes), which accompany the fluctuation of the water level (Pott & Pott 2000).…”
Section: Samplingmentioning
confidence: 99%
“…Os outliers apresentado na região de confluências dos rios se assemelham com o levantamento de Ikeda-Castrillon, et al, (2011) que registraram essa espécie com maior valor de importância, considerada monodominante sobre a diversidade arbórea das ilhas do rio Paraguai na região que vai de Cáceres até a Estação Ecológica de Taiamã. Esses resultados podem estar relacionados a região da planície inundada que tem característica de possuir espécies monodominantes, como também a Erythrina fusca foi destacada por Olivo-Neto, et al, (2020), na região de planície na Estação Ecológica de Taiamã.…”
Section: Discussionunclassified